Legal Development in the Overcoming Overfishing in Indonesian Coastal Areas - Roisah, Kholis; Rahayu, Rahayu; Yusliwidaka, Arnanda; Mubarok, Zaki; Buditama, Ajar (Universitas Negeri Semarang, 2023)
Indonesia, as a vast island state surrounded by extensive seas, holds a strategic advantage in the maritime sector. The coastal areas, rich in resources, play an indispensable role in the lives of numerous Indonesians. Despite the abundance of resources, the well-being of the population faces uncertainties attributed to management challenges. A prominent issue exacerbating the decline in the coastal ecosystem and diminishing productivity is the phenomenon of overfishing. Characterized by the excessive extraction of fish beyond their capacity to replenish, overfishing poses a severe threat to coastal areas. This unsustainable practice is rooted in legal ambiguities, conflicts in authority, and the bio-geophysical degradation of resources within coastal zones. The detrimental consequences of overfishing necessitate immediate attention and intervention to preserve coastal ecosystems and secure the livelihoods of those reliant on them. Addressing these challenges, the focus of this research is on preventing the widespread occurrence of overfishing in coastal areas and mitigating the impacts of existing overfishing activities. The primary strategy proposed involves the development of a robust legal framework for the management of coastal areas. Through the establishment of clear legal guidelines, resolution of uncertainties, and mitigation of conflicts in authority, this research aims to lay the groundwork for sustainable and responsible practices in coastal resource management. The research aims to provide valuable insights that contribute to the enhancement of coastal area management, ultimately fostering ecological sustainability and improving the welfare of communities dependent on these vital resources. By delving into the complexities of coastal resource management, this study seeks to enrich the discourse surrounding sustainable practices, thereby facilitating informed decision-making and policy development in the quest for a harmonious coexistence between human communities and coastal ecosystems in Indonesia.